Sustainability of Water Supply Projects - Dahal, Dhundi Raj (NPRC Journal of Multidisciplinary Research, 2024)
Sustainability is one of the major issues for Water Supply and Sanitation activities/ projects. The project should have the measuring tools for the sustainable part. Water supply is one of the basic needs for human beings with all living things may come first air then water or soil in the universe to sustain. Sustainability indicators of water supply projects was determined by three major dimensions (i) technical, (ii) Socio-environmental, and (iii) Institutional [15]. Other aspects, functionality has divided with requirements, actions, and results. Sustainability is the combination of functionality index and sustainability dimensions on a fifty-fifty percent shearing base. The research has developed sustainability tools on the basis of available literatures and practical experiences. The tools have developed. The project study has to take consideration for the sustainability from the pre-feasibility study, feasibility, detail study.